Introducing the Urban Community Health Center (UCHC) as a Nascent Local Model: Will it be a Linchpin in the Health Sector Reform in Iran? - Mohammad Hadi Imanieh; Ahmad Kalateh Sadati; Mohsen Moghadami; Abdulrasool Hemmati (Kerman University of Medical Sciences, 2015)
Over the past three decades, the Iranian health system has undergone a wide range of reforms. This period has been associated with changes that have helped improve Iran's health system. The most visible breakthrough has been the establishment and improvement of Primary Health Care (PHC) with an emphasis on rural regions (i.e. rural health centers and rural Health Houses), which represented a condition highlighting the potentials of Behvarz (i.e. community health worker) in PHC. The PHC model is composed of eight elements including: health education, vaccination, mother and child care, nutrition, environmental health, control of endemic and common diseases, epidemic control, and essential drugs. This period has led to remarkable achievements in various areas from prevention to treatment (1,2).